Poet-Composer Collaborations in Modern Egyptian Song: A Social Network Analysis Approach to Music History - Michael Frishkopf (Journal of Cultural Analytics)
In this paper I formulate and apply a social network analysis methodology for understanding the history of song on Egyptian radio. Music is a massively relational cultural form, involving interactions among composers, poets, arrangers, conductors, and performers, among others. The reality of music history thus emerges as a complex network of relationships, unfolding and changing over time. Song production, in particular, centers on poet-composer-singer collaborations. Many Arab music histories highlight narratives of the stars, presented in historical and cultural context, but neglect the broader network of productive relationships. However many important musical figures are not celebrities, and the full complexity of the non-linear network can only be grasped holistically, including big data empirical analysis, not pointillistically through case studies of celebrities. Such holistic analysis can reveal surprising emergent, structural patterns that are not apparent in any single narrative. Social network analysis (SNA) offers a powerful suite of tools enabling such an approach, including metrics for centrality and the detection of cohesive subgroups. Starting with a large dataset of songs broadcast on Egyptian radio, I extract a network of poet-composer collaborations, and apply SNA algorithms to reveal its social structure. I then interpret that structure in light of wider socio-cultural and historical factors. In this way, my paper both sheds light on Egypt’s musical history, and supplies a model and method that may be applied, mutatis mutandis, to other musical domains.